Analisis Kelayakan dan Kesiapan Usaha Mikro dalam Pengajuan Sertifikasi Halal : Studi Kasus Usaha Es Cincau - Vina Rakhmawati; Cory Vidiati; Ahmad Munajim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the business feasibility and readiness of micro enterprises in applying for halal certification, focusing on a case study of mobile grass jelly drink vendors. This research uses a qualitative approach with a case study method. The subjects of this study consist of two vendors who have been running their businesses for a considerable period. Data were collected through direct interviews. The results show that the business is feasible in terms of economic and operational aspects, as indicated by its sustainability since 2006 and the existence of regular customers. However, in terms of management and legal aspects, the business still faces limitations, such as incomplete financial records and the absence of business legality. Regarding halal certification readiness, the vendors are aware of its importance but still lack sufficient understanding of the procedures and administrative requirements. In conclusion, there is a gap between the economic feasibility of the business and its administrative readiness for halal certification. This study is expected to provide an overview of micro-enterprise conditions and contribute to improving halal certification readiness.